Dextro Rotation of Uterus at Term: Classical Caesarean Section Through Posterior Uterine Wall - SHAMSA HUMAYUN, SADIA AHSAN (Journal of Fatima Jinnah Medical University, 2018)
Uterine torsion is rare obstetrical complication up till 1992. Only 212 cases have been reported in literature. Here we present a case of 26 years old lady with history of previous II LSCS. She was 38 weeks pregnant with abruptio placenta + IUD baby. On opening the abdomen, she had Dextro rotation of uterus through an angle of 180. Baby was delivered through classical posterior uterine wall incision. Dextro rotation was corrected. Bilateral tubal ligation was done.